HUBUNGAN JARAK KEHAMILAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III DI PUSKESMAS BAGELEN KABUPATEN PURWOREJO - Nurma Ika Zuliyanti; Krisdiyanti (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
Anemia in pregnant women increases the risk of blood loss during delivery, making it more difficult to fight infection. Pregnancy interval is one of the factors that influence anemia. Based on the results of a preliminary study at the Bagelen Public Health Center, Purworejo Regency, 20 pregnant women, 8 anemic pregnant women, 12 non-anemic pregnant women. The purpose of the study was to determine the relationship between gestational distance and the incidence of anemia in pregnant women TM III at the Bagelen Health Center, Purworejo Regency. The research method uses a correlation study, a cross sectional research design, using primary and secondary data. The population is 112 pregnant women, purposive sample sampling technique with a total sample of 87. Data analysis using chi square test. The results showed that the pregnancy interval 2 years was not anemic 35 pregnant women, anemia 13 pregnant women. Pregnancy interval <2 years without anemia 15 pregnant women, anemia 24 pregnant women. The results of the statistical chi square test (10.541) p value = 0.001, the contingency coefficient was 0.327, so that there was a relationship between pregnancy distance and the incidence of anemia in pregnant women with TM III at the Bagelen Health Center, Purworejo Regency.